AMINO-ACID-SEQUENCE OF TSTX-V, AN ALPHA-TOXIN FROM TITYUS-SERRULATUS SCORPION-VENOM, AND ITS EFFECT ON K+ PERMEABILITY OF BETA-CELLS FROM ISOLATED RAT ISLETS OF LANGERHANS - Marangoni, S.; Toyama, M. H.; Arantes, E. C.; GIGLIO, JR; Dasilva, C. A.; Carneiro, E. M.; Goncalves, A. A.; Oliveira, B. (Elsevier B.V., 1995)
Highly purified Tityustoxin V (TsTX-V), an alpha-toxin isolated from the venom of the Brazilian scorpion Tityus serrulatus, was obtained by ion exchange chromatography on carboxymethylcellulose-52. It was shown to be homogeneous by reverse phase high performance liquid chromatography, N-terminal sequencing (first 39 residues) of the reduced and alkylated protein and by polyacrylamide gel electrophoresis in the presence of sodium dodecylsulfate and tricine. Following enzymatic digestion, the complete amino acid sequence (64 residues) was determined. The sequence showed higher homology with the toxins from the venoms of the North African than with those of the North and South American scorpions. Using the rate of Rb-86(+) release from depolarized rat pancreatic beta-cells as a measure of K+ permeability changes, TsTX-V (5.6 mu g/ml) was found to increase by 2.0-2.4-fold the rate of marker outflow in the presence of 8.3 mM glucose. This effect was persistent and slowly reversible, showing similarity to that induced by 100 mu-M veratridine, an agent that increases the open period of Na+ channels, delaying their inactivation. It is suggested that, by extending the depolarized period, TsTX-V indirectly affects beta-cell voltage-dependent K+ channels, thus increasing K+ permeability.
Keywords: ALPHA-TOXIN; PRIMARY STRUCTURE; RB-86(+) OUTFLOW; ISLETS OF LANGERHANS; (RAT); (TITYUS SERRULATUS)